PENAPISAN DAN PEMANFAATAN RHIZOBAKTERI TANAMAN JAGUNG (Zea mays) SEBAGAI INOKULAN PEMACU TUMBUH TANAMAN - Debby Widiyanti; Sri Pujiyanto; Agung Suprihadi; Mamik Setyowati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Maize (Zea mays) is the second most important food commodity after rice plants. The role of the corn crop in agricultural commodities encourage the use of biological fertilizers to increase crop productivity of maize. The use of biological fertilizers open opportunities using rhizosphere bacteria as inoculants boosters grow plants.This study aims to obtain bacterial isolates from the rhizosphere of maize (Zea mays), characterize the morphology and biochemical properties of the ability to produce IAA, provide nutrients such as N and P and to get a bacterial inoculant boosters grow corn. Rhizosphere bacteria were isolated using SEA media (soil extract agar). Isolates that have the ability to produce IAA, tether N and high P solvents tested against corn seed germination and applied in a phase of plant growth. The results showed there were 24 isolates corn crop rhizosphere dominated by gram-positive bacteria and shaped basil capable of producing IAA grading 4,83 to 125,84 ppm. 16 rhizosphere bacterial isolates capable of dissolving phosphate with phosphate solubility index ranged from 2,1 to 4,6. 18 rhizosphere bacterial isolates capable of tether N with the highest N tether capacity of 2,8 x 10 3 CFU/ mL. Application 3 selected bacteria such as J11, J16 and J19 as inoculants are not able to increase the growth of corn plants compared to control water. Keyword :Maize, Rhizosphere, The growth of corn plants.